The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2022
DOI: 10.3390/healthcare10071341
|View full text |Cite
|
Sign up to set email alerts
|

The Importance of Behavioral and Native Factors on COVID-19 Infection and Severity: Insights from a Preliminary Cross-Sectional Study

Abstract: The COVID-19 pandemic has had a major impact on a global scale. Understanding the innate and lifestyle-related factors influencing the rate and severity of COVID-19 is important for making evidence-based recommendations. This cross-sectional study aims at establishing a potential relationship between human characteristics and vulnerability/resistance to SARS-CoV-2. We hypothesize that the impact of the virus is not the same due to cultural and ethnic differences. A cross-sectional study was performed using an … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
20
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 26 publications
(24 citation statements)
references
References 158 publications
0
20
0
Order By: Relevance
“…To date, there have been in excess of 550 million confirmed cases and over six million deaths in more than 200 countries [ 1 ]. The COVID-19 pandemic dramatically affected the world’s economy [ 2 , 3 ] and impacted all aspects of the socioeconomic spectrum. The global response to the pandemic, in terms of government policy, vaccination development and availability, slowed the spread of COVID-19 and its effects [ 4 , 5 , 6 ].…”
Section: Introductionmentioning
confidence: 99%
“…To date, there have been in excess of 550 million confirmed cases and over six million deaths in more than 200 countries [ 1 ]. The COVID-19 pandemic dramatically affected the world’s economy [ 2 , 3 ] and impacted all aspects of the socioeconomic spectrum. The global response to the pandemic, in terms of government policy, vaccination development and availability, slowed the spread of COVID-19 and its effects [ 4 , 5 , 6 ].…”
Section: Introductionmentioning
confidence: 99%
“…Figure 3 , Figure 6 and Figure 7 provided a more accurate and detailed view of the level of mortality risks by province. The provinces of Batna and Tizi Ouzou showed higher risks, and this means that besides the population density component already demonstrated [ 20 ], there are other factors related to the distribution of the number of deaths in the country [ 10 ]. The three provinces with the largest population density (Algerirs, Oran, and Constantine) were at the forefront of the ranking with the provinces of Tizi Ouzou, Setif, and Batna.…”
Section: Resultsmentioning
confidence: 99%
“…Therefore, studying the pandemic is essential for acquiring comprehensive analytical knowledge about the new phenomenon and finding appropriate measures to control the spread of the disease [ 9 , 10 ], also based on previous experience in infectious diseases control [ 11 ]. Global efforts have resulted in identifying several antiviral drugs, and a few vaccines have been developed [ 12 , 13 ], however, no clinically approved treatments have been identified, despite many trials of drug repurposing [ 14 , 15 ].…”
Section: Introductionmentioning
confidence: 99%
“…An example is a study by Aouissi et al, which showed that strong immunity due to healthy lifestyle measures was associated with a reduced probability of contracting the COVID-19 virus. They also demonstrated that eating healthy, sleeping well, and regular physical activity can better enhance multiple disease prevention and outcomes [ 18 , 19 ]. Another study on children by Scapaticci et al discussed that being able to consume enough vitamins and minerals, which have antiviral properties and may lessen the intensity of symptoms, is essential for enhancing immune responses [ 20 ].…”
Section: Discussionmentioning
confidence: 99%